Designed synthesis of Co-doped sponge-like In2O3 for highly sensitive detection of acetone gas. Issue 12 (14th February 2019) - Zhang, Xiaole; Song, Dalei; Liu, Qi; Chen, Rongrong; Liu, Jingyuan; Zhang, Hongsen; Yu, Jing; Liu, Peili; Wang, Jun
Abstract : Materials based on Co-doped sponge-like In2 O3 with high sensing properties were fabricated for easier detection of acetone gas. Abstract : Pure and 1–4 mol% cobalt doped indium oxide (Co-doped In2 O3 ) sponge-like microstructures with high specific surface area were fabricated by a simple and environmentally friendly hydrothermal method. The specific surface area and porosity of Co-doped sponge-like In2 O3 microstructures can be regulated through the modulation of Co/In molar ratios. The as-prepared sensors based on Co-doped In2 O3 exhibit favorable gas sensing properties toward acetone gas; their porous structure can create more adsorption sites for the adsorption of oxygen molecules and the diffusion of the target gas, leading to significant improvement in sensing performance. In particular, 3 mol% Co-doped In2 O3 presents the greatest response to acetone vapor at 240 °C, which is about 3.25 times higher than that of pure In2 O3 . The sensor also exhibits rapid response-recovery time (1.143 s/37.5 s), low detection limit (2.76 at 5 ppm), good reproducibility and high selectivity, making it a promising material for acetone detection.